Relationship Between Plasma Leptin Levels and Airflow Limitation in the Small and Medium Airways in Young Adults - Garcia-Herrera, C (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background/Objectives: To determine the relationship between plasma leptin levels and airflow limitation (AFL) in the small and medium airways of young adults according to their body composition (BC). Methods: To determine AFL, the following measurements were taken: forced expiratory volume in the first second (FEV1), forced expiratory flow between 25–75% (FEF25–75%), airway resistance (Raw), and specific airway resistance (sRaw). The measured BC variables were body mass index (BMI), body fat percentage (%BF), trunk fat percentage (TF%), and fat-free mass (FFM). Plasma leptin was measured using the ELISA technique. Results: In total, 83 participants (40 male and 43 female) aged 21.55 ± 2.08 years were evaluated. Leptin was significantly higher in women than men (p < 0.01). When relating leptin to lung function variables, FEV1 and FEF25–75% showed a significant inverse relationship (p < 0.01), and Raw and sRaw showed a direct and significant relationship (p < 0.01). Female participants with a BF% and leptin higher than their p75 were observed to have a higher risk of increased sRaw (OR = 1.0; OR = 1.15, respectively), regardless of age, and participants with an FFM% higher than their p75 had a lower risk of increased sRaw (OR = 0.71), regardless of gender and age. Conclusions: There is an inverse relationship between FEV1, FEF25–75%, and a direct relationship between Raw and sRaw with leptin. For female participants with a higher BF%, higher FFM%, and leptin, the risk of developing Raw and sRaw was found to be modified. © 2025 by the authors.
Keywords: body composition; leptin; airflow; airway; young adult